Design of A Decision Support System for Students' Extracurricular Choices using the TOPSIS Method at SMKN 1 Bukit Sundi - Afdal; Yendi Putra; Yulhan; Etika Melsyah Putri (Research Collaboration Community (RCC), 2025)
Education not only emphasizes academic excellence but also requires the development of students' character, talents, and soft skills. Extracurricular activities play a crucial role in providing students with opportunities to explore their potential beyond the classroom. However, students often encounter difficulties in selecting the most suitable extracurricular activity, which may result in low motivation and reduced participation. To address this issue, a web-based Decision Support System (DSS) was developed using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The system considers multiple criteria, namely interest, talent, academic achievement, parental support, physical condition, and equipment cost, to generate objective recommendations. The research was conducted at SMKN 1 Bukit Sundi with seven extracurricular alternatives, including Futsal, Volleyball, Pramuka, Paskibra, Marching Band, OSIS, PMR, and Randai. The system was implemented using PHP and MySQL, providing an automated process of normalization, weighting, calculation of ideal solutions, and ranking. Results showed that Futsal achieved the highest preference value (0.755846), followed by Volleyball and Pramuka, while Randai ranked lowest with a value of 0.223794. These findings indicate that student preferences are strongly aligned with sports and leadership activities, while traditional art forms are less favoured. The system proved to be consistent with manual calculations and successfully enhanced transparency, efficiency, and accessibility in extracurricular selection. Compared to alternative methods such as SAW, TOPSIS offered greater flexibility by accommodating both benefit and cost attributes simultaneously. This study contributes practically by providing a tool that supports schools and students in decision-making, and academically by extending the application of TOPSIS in vocational education.